Pengaruh Kompensasi, Iklim Kerja, dan Kepemimpinan Transformasional terhadap Kepuasan Kerja serta Implikasinya pada Loyalitas Kerja - Diar Fachmi R Chaidar (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2016)
The purpose of this study was to analyze the effect of compensation, work climate and leadership transformational on job satisfaction and loyalty implication at work on the middle manager. This Research is done by using descriptive methods and verification. The sampling technique used proportional random sampling with a sample of 400 respondents of the study. Analysis tool that is used is to use Path Analysis. Conclusions are: 1) Compensation, work climate and transformational leadership and job satisfaction and company loyalty middle manager in the manufacturing sector foreign capital Karawang, Bekasi, Bogor and Tangerang categorized either; 2) Closeness of the relationship between the independent variables, have levels of the relationship medium; 3)There is a significant influence of all independent variables (call it whatever the independent variable) on job satisfaction influences middle manager; 4) There is a significant influence of the variables of job satisfaction on loyalty middle manager working in Karachi, Jakarta, Bogor and Tangerang.